2013
DOI: 10.1021/jp4046963
|View full text |Cite
|
Sign up to set email alerts
|

A Reversible Molecular Switch Based on the Biphenyl Structure

Abstract: DFT calculations were performed on a biphenyl-based molecule bonded to gold nanoleads in order to evaluate its potential as a reversible molecular switch. The torsion angle (φ) between the aromatic rings may be controlled by means of reducing a disulfide functionality that bridges the two rings, giving rise to a "closed" species (disulfide bridge oxidized, φ ∼ 28°) and an "opened" species (disulfide bridge reduced, φ ∼ 65°). The mechanical properties of the nanojunction formed by this molecular species sandwic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 53 publications
(86 reference statements)
1
28
0
Order By: Relevance
“…39 There, it was shown that this metal/molecule hybrid nanojunction can be stretched by ∼ 8.5Å, before it finally breaks. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 reported in Ref.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…39 There, it was shown that this metal/molecule hybrid nanojunction can be stretched by ∼ 8.5Å, before it finally breaks. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 reported in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 reported in Ref. 39 on the thermodynamics of the reduction reduction and the transport properties of the species involved were based on the first minimum encountered along the stretching pathway.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations